ANALISIS KESULITAN SISWA PADA JENJANG SD DAN SMP DALAM MEMAHAMI PEMBELAJARAN IPA - Ahmad Dedi Marzuki; Fena Prayunisa (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The research objective was to analyze the difficulties of elementary and junior high school students in learning science. The subjects in this study were students of class IV SD Negeri 4 Danger and class VII SMP Negeri 1 Masbagik. The sample in this study was determined by purposive random sampling with superior schools and classes that had an average grade that had not yet reached the KKM. Data collection techniques used by researchers are observation, tests, interviews, and documents. The type of observation used by researchers is passive participation observation, that is, researchers make observations by coming to the research site, but are not involved in the activities carried out (Sugiyono, 2019). The interviews in this study were semi-structured interviews. In this study the test method was used to find out the difficulty of learning science, namely understanding the concept of science in class IV SD Negeri 4 Danger and class VII SMPN 1 Masbagik which consisted of 15 essay questions. The results of this study found several factors causing student learning difficulties including external factors. The role of the teacher, the role of peers, and the role of parents. Another factor is the internal factor, namely the interest and learning habits of students.